Factors supporting digital pedagogical competence of primary education teachers in Indonesia - Bentri, Alwen; Hidayati, Abna; Kristiawan, Muhammad (Frontiers in Education, 2022)
Digital pedagogical competence is an ability that needs to be developed by teachers to instruct their students in the 4.0 industrial revolution era of the 21st-century. In West Sumatra, the creative capabilities of instructors are inadequate. Hence, they must be able to apply different approaches to learning. The aim of this research is to analyze the digital pedagogical competence of primary education teachers in West Sumatra and its effect on the potential to create digital products. It was conducted using the sample size from three areas, namely Padang, Bukittinggi, and Solok cities, whereby the total being 94 teachers based on their education level, age, and gender. Moreover, the data collection technique is questionnaires that have been tested for validity and reliability. Fur-thermore, the results show that there are factors supporting teachers’ ability to create digital tools in terms of analysis and evaluation. However, for these, it is recommended to provide structured training for the development of digital pedagogy abilities.